Dimensions of Islamization in the Development of Science - Muslih, Mohammad; Perdana, Martin Putra; Sutoyo, Yongki (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
Scientific problems are indeed an interesting issue to be researched. Moreover, seeing the development of science globally in the West is not based on God’s revelation and guidance. Although this knowledge can then produce technology that facilitates human life’s affairs, this convenience is accompanied by nature exploitation and destructive moral degradation. This Western view of life is certainly not compatible with the monotheistic Islamic point of view. Given the differences in seeing reality and truth, scientific studies need to be reconstructed and linked to religion as a form of applicative integrative method that does not place religion as a foreign matter in science. In response, Muslim scholars offered alternative ideas in a discourse on the integration of religion and science called the Islamization of contemporary science. With the critical analysis method, the authors sought to reveal the dimensions of Islamization that could touch the root of the science problem (epistemological) and answer the scientific development problems. Islamization is expected to be a universal framework that not only can be used by Muslims but also non-Muslims.